2018
DOI: 10.1364/ao.57.004955
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of WSe2on red passively Q-switched fiber laser output performance

Abstract: Transition metal dichalcogenides (TMDs) possess a direct bandgap in the visible frequency range and can be applied as attractive visible saturable absorbers (SAs). In this paper, a new TMDs tungsten selenide (WSe)-based red Q-switcher is fabricated and successfully used for Q-switched pulse generation in a red Pr-doped ZBLAN fiber laser. The passive Q-switching fiber laser at 635.2 nm generates a stable pulse with pulse duration of 504 ns and average output power of 4.91 mW as well as a tunable pulse repetitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In fact, the depth of modulation for pulse generation as well as shaping is directly proportional to |β| [57] and consequently, W Se 2 thin-films exhibiting strong Pauli-blocking induced SA behaviour would serve the purpose very efficiently. It has been demonstrated that stable high-energy nanosecond pulses could be generated by employing a few layer W Se 2 sheets (acting as saturable absorber) through passive Qswitching in P r 3+ -doped ZBLAN fiber laser emitting at 635 nm wavelength [58]. In a similar investigation, B. Chen et al have employed an arbitrarily thick W Se 2 film as a saturable absorber for generating Q-switched nanosecond pulses in erbium doped fiber laser [59].…”
Section: (B)mentioning
confidence: 99%
“…In fact, the depth of modulation for pulse generation as well as shaping is directly proportional to |β| [57] and consequently, W Se 2 thin-films exhibiting strong Pauli-blocking induced SA behaviour would serve the purpose very efficiently. It has been demonstrated that stable high-energy nanosecond pulses could be generated by employing a few layer W Se 2 sheets (acting as saturable absorber) through passive Qswitching in P r 3+ -doped ZBLAN fiber laser emitting at 635 nm wavelength [58]. In a similar investigation, B. Chen et al have employed an arbitrarily thick W Se 2 film as a saturable absorber for generating Q-switched nanosecond pulses in erbium doped fiber laser [59].…”
Section: (B)mentioning
confidence: 99%
“…In fact, their properties can be tailored by external voltage or stress and they exhibit strong spin-orbital coupling [28]. Transition metal dichalcogenides have been applied to different laser systems [29]- [34] from 635 nm to 3000 nm, with pulse durations from 500 ns to more than 2000 ns. Finally metal nano-particles (e.g., silver and gold) have also been used as saturable absorbers in fiber lasers [35], [36].…”
Section: Introductionmentioning
confidence: 99%